"It just makes you feel…like you belong finally": people's experiences of the Mildura "Welcome Baby to Country" aboriginal ceremony. (2nd January 2022) - Gilby, Rosemary; Jobson, Laura; Adams, Karen
ABSTRACT: Employing Yarning method, this study describes people's experiences of a Welcome Baby to Country ceremony in Australia. People articulated immediate social and emotional wellbeing benefits via strengthened identity, belonging and connections to family, community and country. The value of cultural re-initiation and continuity for Aboriginal children's programs cannot be underestimated. Settler colonial paradigms are ill-fit, potentially causing lasting damage by undermining a child's development and identity. Embedding meaningful cultural practice will have lifelong benefits for children's cognition, emotional regulation, education, social skills and memory. As children will know: who they are; where they belong and; how to confidently act in the world.